Peran Teknologi Know Your Customer (KYC) dalam Meningkatkan Ketahanan Nasional: Aspek Keamanan dan Hak Asasi Manusia - Rino Rahaditya Syahputra (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
In the current digital era, the implementation of Know Your Customer (KYC) technology has become one of the important solutions to enhance national resilience. KYC functions not only in a business context but also has significant impacts on security and human rights aspects. This article aims to analyze the role of KYC technology in improving national resilience with a focus on the resulting security aspects and the protection of human rights. Through a literature review, this article concludes that while KYC technology contributes positively to strengthening national security, its implementation must be balanced with respect for human rights to create an effective equilibrium.